Thermal studies of residential buildings in hot desert climate in Algeria - Behaz, Amira (Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2018)
The traditional houses (Trad.H) in Ghardaia City in Algeria had been built using traditional construction materials and passive design strategies for the hot desert climate. These thousand year old houses are still standing and conditioning the harsh desert climate while maintaining indoor thermal comfort for its occupants. As of late, two trends of modern housing and construction were observed to have evolved in Ghardaia. Firstly, are the modern houses (Mod.H) following the international style and secondly, the eco-friendly houses (Eco.H) utilizing passive solar design. The Mod.H were observed to implement some of the traditional features but using the modern construction material. Meanwhile, the Eco.H modified closely the features of the traditional construction and materials. The intention of this study was to investigate the thermal performances of the two contemporary houses in relation to the thermal performance of the Trad.H. The argument was to determine whether the Eco.H or the Mod.H provided better indoor thermal comfort in the context of the summer season. Asserting this aim, the study investigated the thermal comfort of Eco.H and Mod.H and compared their performances with Trad.H. The quantitative method was used to measure the thermal comfort of the three types of houses. A field survey was conducted using thermal data loggers installed in three selected houses to record the air temperature and relative humidity of the outdoor and indoor spaces. Data collection was carried out in July, which was one of the hottest months. The study indicated that passive solar techniques employed in Trad.H could reduce indoor temperatures for comfortable indoor environment to the occupants. It was also observed that the indoor temperature of the Eco.H was almost similar to that of Trad.H, which is 3 to 5 °C cooler than the Mod.H. The study ascertained that designs of buildings with traditional construction and material played significant roles in moderating the indoor environment when the outside climate of the Algerian desert becomes unbearable. Inadvertently, energy for cooling was saved, creating a great impact not only on the economy both at national and global levels, but on an environmental level as well.